Cataloging the genetic diversity of bats (order : chiroptera) in Turkey - Yiğit, Zirve. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2012., 2012)
In this study, 26 bat species from Turkey and surroundings were investigated with the cytochrome-oxidase subunit I (CO1) barcoding method. Twelve CO1 sequences from Barcode of Life Database (BOLD) and Genbank and 134 specimens from Turkey and surroundings were analyzed. Neighbor-joining (NJ) and maximum-likelihood (ML) trees were generated and haplotype networks were prepared. For each species sequences were identified in BOLD, and a BOLD tree of each species was obtained for intraspecific and interspecific comparisons. Previous studies regarding Turkish bat fauna were reviewed to make species classifications based on morphological taxonomy. We found that at least six species have high intraspecific divergence and are good candidates for discovery of cryptic species or subspecies for the Turkish population. We found two species show high intraspecific divergence between the Turkish population and other populations. We conclude that, at least for bats, CO1 barcoding is a promising method for discovery of new taxa, as well as being a quick and efficient identification method.
Keywords: Bats -- Turkey.; Population genetics.